Four-Cable-Plane Spatial Cable Stayed Bridge with Two-Amplitude Curved Deck for Canyon-River - Wang Jilin; Xu JinFa (E3S Web of Conferences, 2021)
On the basis of the original design of Ruck Bridge by Mr. Lin Tongyan, this paper modifies the single-amplitude curved cable-stayed bridge of Ruck Bridge to be an elliptical ring main beam of two-amplitude curved deck, with a duck-egg-shaped arch tower and a spatial cable net with four cable planes, to form a spatial four-cable-plane two-amplitude-curve cable-stayed bridge for the canyon-river topography, so as to improve the structural stress performance of the curved-beam cable-stayed bridge, promote the traffic function and improve the landscape. Combined with the 400m-span New Ruck Cable-stayed Bridge, engineering parameters are designed, a Midas finite element analysis model is established, and the dynamic modal analysis is carried out to verify the structural superiority of this new four-cable-plane spatial cable-stayed bridge with two-amplitude curved deck.